A Short-Run Measure of the Relative Economic Contribution of Direct Foreign Investment - Koo, Anthony Y. C. (The Review of Economics and Statistics, 1961)
CCORDING to a recent estimate by the A Department of Commerce, the United States direct foreign investments are in excess of $22 billion and are expanding at a record rate. How much do we know about the impact of United States enterprises abroad on the host countries, and what is their economic contribution in particular? Aside from a few isolated case studies,' our knowledge is extremely limited. This is perhaps because direct foreign investment is of relatively recent origin. On the basis of total investment made by Britain during the nineteenth century, bonds and preferred stocks comprised indeed no less than three-quarters of the outstanding total in I9I3 2 As a result, there is a lack of concensus among economists of what constitutes economic contribution, let alone an acceptable measure of it. It is argued that direct foreign investment exerts an impact on almost every aspect of life in the recipient country.3 Measurement in some cases is extremely difficult if not impossible, and precise statistics which would illustrate the relationships are in general not available. For example, some foreign enterprises contribute to the opening of new frontiers, resource discovery, and creation of social capital in the form of road building, provision of public utility services, etc., and most of the foreign manufacturing operations engage in the training of skilled and semi-skilled workers. In this way, the foreign establishments, consciously or not, have created an ever-growing supply of many of the modern skills which are indispensable to the economic and social progress of the host countries. stimulation of more private investment within less developed countries is intimately related to the development of a spirit of enterprise among the natives themselves. Here again, the foreign companies can make an important contribution. They provide living examples of the material rewards of private enterprise and its importance to the community, and they also familiarize the natives with modern business attitudes and activities and disseminate the necessary managerial know-how. In short, such direct foreign operations give the wage and market economy its decisive start, with an attendant loosening of the bonds of the static self-sufficient agrarian societies. benefits presented above are undoubtedly valid. broad social and economic consequences of transformation should not be passed over lightly. But the nature of these impacts is generally regarded as belonging to the long-term effects of an industrialization process. In short-run analysis, economists customarily confine themselves to the immediate impact of investment in terms of changes in production, employment, and income. In this respect, the statistical survey conducted by the Department of Commerce on the various phases of United States business operations in Latin America is worthy of attention, because the survey provides, for the first time, data on production, income, and capital accumulation in this area.4 However, comprehensive as the data are, with figures classified by industry and by country, there is no criterion in the survey by which we can arrive at an over-all evaluation of the relative contributions by United States operations in different industrial groups and/or countries. purpose of this paper is to utilize the data in the survey in such a way as to make a composite ranking possible. In attempting to do this, we shall first sort out the data in accordance with four criteria which we shall lay down I See six case studies on U.S. business performance abroad published by the National Planning Association. They are Sears, Roebuck de Mexico, Casa Grace in Peru, Philippine American Life Ins. Co., Creole Petroleum Corporation in Venezuela, Firestone Operations in Liberia, and Stanvac in Indonesia. 2R. Nurkse, The Problem of International Investment Today in the Light of Nineteenth-Century Experience, Economic Journal, LXIV (December I954), 744-58. 8For a more detailed listing of possible principal benefits of foreign direct investment to the host country, see the policy statement of the National Planning Association in its series of case studies referred to above. ' U.S. Investm6nt in Latin America (I957).